CYP2W1 polymorphism: functional aspects and relation to risk for colorectal cancer. (October 2013) - Stenstedt, Kristina; Travica, Sandra; Guo, Jia; Barragan, Isabel; Pors, Klaus; Patterson, Laurence; Edler, David; Mkrtchian, Souren; Johansson, Inger; Ingelman-Sundberg, Magnus
Aim: This study aims to investigate the possible association between the risk of colorectal cancer (CRC) and allelic variants of CYP2W1 and their functional properties.Materials & methods: The distribution of three different CYP2W1 alleles ( CYP2W1*1, CYP2W1*2 and CYP2W1*6 ) in 1785 CRC patients and 1761 healthy blood donors was determined using the TaqMan ® (Applied Biosystems, CA, USA) allelic discrimination assay or allele-specific amplification. Corresponding gene products (CYP2W1.1, CYP2W1.2 and CYP2W1.6) were expressed in human colon cancer SW480 cells and their activities towards two different substrates, the duocarmycin analogs ICT2706 and ICT2726, were monitored.Results: No significant differences in the distribution of CYP2W1*1, CYP2W1*2 and CYP2W1*6 alleles were found between CRC patients and controls. The CYP2W1.1, CYP2W1.2 and CYP2W1.6 variant enzymes were expressed at the similar levels in the transfected SW480 cells and had comparable kinetics in terms of the metabolism of the duocarmycin ICT2726, as well as in the bioactivation of ICT2706 into a cytotoxic product.Conclusion: These epidemiological data obtained from a large population of CRC patients and controls cannot confirm the previously suggested decreased risk for CRC among carriers of CYP2W1*2 . On the molecular level, this conclusion is further supported by the similar catalytic characteristics of the CYP2W1.1, CYP2W1.2 and CYP2W1.6 variants of CYP2W1. Original submitted 19 March 2013; Revision submitted 15 July 2013